(untitled) (Research, Society and Development, 2023)
The biological control using entomopathogenic fungi is an alternative tool in integrated pest and disease management that attack the crops, reducing the environmental risks caused by chemical control techniques. In this context, this work aimed to evaluate the compatibility of pesticides on the microorganism Beauveria bassiana. The experiment was conducted in a completely randomized design with a 7 x 3 factorial arrangement with three replications. First factor corresponded to the doses, and the second referred to the pesticides (Fipronil, Chlorpyriphos, Imidacloprid + Fipronil, Imidacloprid, Chlorantraniliprole), and two fungicides (Hexaconazole and Propiconazole). The microorganism was developed in PDA medium. Doses at different concentrations were used with an automatic pipette as (1/2RD; RD; 2RD). The plates were incubated in a BOD for 12 h at 25 ± 2 °C. The parameters evaluated were colony diameter, fungal growth inhibition and sporulation of the Beauveria bassiana. The results showed that tested insecticides were compatible with the fungus except Chlorpyriphos. The fipronil at 1/2RD, RD and 2RD showed lower rate of inhibition respectively 37,5%; 44,44% and 50,26%. The fungicides Hexaconazole and Propiconazole were toxic because were completely inhibitory the fungal growth at all the concentrations. It concludes the pesticides Fipronil, Imidacloprid + Fipronil, Imidacloprid, Chlorantraniliprole can be used in integrated pest and disease management programs.